Intrinsic shuttle suppression in lithium-sulfur batteries for pouch cell application - Weller, Christine; Thieme, Soeren; Haertel, Paul; Althues, Holger; Kaskel, Stefan (Journal of The Electrochemical Society, 2017)
A novel electrolyte approach for a lithium-sulfur secondary battery is presented, realistically portrayed on pouch cell level, with its decisive element being a new electrolyte system, a mixture of a hydrofluoro ether and sulfolane. The hereby suppressed polysulfide solubility enables high discharge capacities and requires only very low electrolyte excess (< 2.6 μLmgS-1) achieving high coulomb efficiencies above 94% (capacity retention of 77% over 40 cycles) without the necessity of adding lithium nitrate for shuttle suppression. Due to the low volatility, this adopted electrolyte concept promises significant benefits for large operational battery units.
CRIS-Team Scopus Importer:2022-04-14